Стан йодної забезпеченості вагітних і новонароджених на Сході України - Бєлих, Н. А.; Валієв, О. А.; Сапельников, О. Я.; Сапельникова, Л. Я.; Білошицький, О. О.; Коваленко, М. М. (Clinical Endocrinology and Endocrine Surgery, 2011)
The article deals with the data of interviewing and examination of pregnant women and regional results of TSH-screening in newborns. in 2009. It was proved that iodine deficiency in intake and absence of individual iodine prevention lead to decrease median of ioduria and hypothalamic-thyroid dysfunction in pregnant and high rate of neonatal hyperthyrotropinemia in newborns. The conclusion the iodine supplementation necessity in risk groups (pregnant, children and nursing women) was made.